The role of aging on the cause, type and cost of construction injuries - Schwatka, Natalie V., author; Rosecrance, John C., advisor; Butler, Lesley M., committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2011)
As older workers continue to delay retirement, understanding the health and safety needs of an aging workforce will be critical over the next twenty years. The goal of the project was to determine the impact of age on workers in the construction industry as age relates to selected workers' compensation variables. Descriptive and multivariate analysis of over one hundred thousand workers' compensation construction industry claims for the state of Colorado was conducted to understand the relationship between the claimant age and workers' compensation costs by the causes and types of injuries and illnesses. The results indicated that the cost of injuries among older workers was greatest for indemnity costs alone, where there was a 3.5% increase in the indemnity cost of a claim for each year increase in age. Workers over the age of 65 were injured most frequently from falls, slips and trips and workers aged 35 to 64 were injured most frequently from strains. Though repetitive motion causes of injuries were not frequent among all age groups, they resulted in a 6.8% increase in the indemnity cost of a claim for each year increase in age. Strains were the most common type of injury for workers over the age of 35 but workers over the age of 65 experienced strains and contusions at similar frequencies. The shift towards an older work force will result in an increase in the proportion of occupational injuries among older workers, which will result in increased costs associated with lost work time and disability. Employers who wish to remain competitive must effectively manage a health and safety program that acknowledges the needs of the aging worker. Encouraging companies to address the specific needs of older workers is the first step in reducing the frequency and cost of occupational injuries related to older age.
Keywords: aging workforce; construction industry; occupational injury; occupational injury cost; older workers; workers' compensation